Reconstitution of power and democracy in the age of capital globalization - Costilla, Lucio Fernando Oliver (2000)
Focuses on the Latin American nations with the largest economies i.e. Argentina, Brazil, Chile, Mexico and Venezuela. Reflects on the historical consequences of the policies and measures undertaken by the major Latin American countries to integrate their economies into the global economy during the past decade and a half. Considers the limits, contradictions, and possibilities of a policy of the state and society of seeking positive integration of Latin America into the global market.